The Completion of Misdemeanor through Rembuk Pekon in Lampung Province - Zulfi Diane Zaini; Lintje Anna Marpaung; Zainab Ompu Jainah; Thia Remona Febrianti; Sija Putra Rulanda (Fiat Justisia: Jurnal Ilmu Hukum, 2020)
The resolution of a criminal offence does not have to be carried out through legal channels. Still, it can be done in the spirit of restorative justice, one of which uses the principle of ADR (Alternative Dispute Resolution) or (win-win solution) through the Rembuk Pekon which means through consensus agreement. This study aims to determine what crimes can be resolved with the Pekon consultation, how the process is resolved, and what the legal consequences are. This study uses an empirical normative method by examining the methods, norms, rules and primary data through observation and interviews, the results of the study indicate that the types of criminal acts that can be resolved with Rembuk Pekon include minor criminal offences Article 302, Article 352 paragraph (1), Article 364, Article 373, Article 379, Article 482, Article 315, Article 407 paragraph 1, and the criminal offence of complaint Article 284 of the Criminal Code. So in this study will discuss how the process of resolving minor criminal cases through the Rembuk Pekon and the authors have a suggestion that the police should implement the Rembuk Pekon to prioritize the principles of professional, modern and reliable, this so that the implementation of the Rembuk Pekon can run optimally.